Organization of the Use of Moscow Cultural and Historical Heritage in Tourist Activities - KRYUKOVA, Elena; KHETAGUROVA, Valeriya; MOSALEV, Anton; MUKHOMOROVA, Irina; EGOROVA, Elena (Journal of Environmental Management and Tourism; Vol 10 No 4 (2019): JEMT Volume X Issue 4(36) Summer 2019DO - 10.14505//jemt.v10.4(36).07, 2019)
Analysis of scientific sources on the problems of cultural tourism shows that there are significant theoretical developments on this issue. However, despite the intensification of research efforts aimed at analyzing the development of cultural tourism, certain aspects of the regulation and development of this direction remain, in the authors’ opinion, insufficiently studied. The need to develop evidence-based practical recommendations to promote the national cultural tourism product at the national, federal and local levels currently exists. The paper defines the role of the business sector in the use of cultural heritage. Insufficient knowledge on the matter, as well as the relevance and the theoretical and practical significance of the use of cultural heritage in the tourism industry, determine the choice of the topic, the purpose of the study and its objectives